Aromatic plants from Yungas. Part III. Composition and antimicrobial activity of Myrrhinium atropurpureum Schott var. octandrum Bentham essential oil - Rotman, Alicia Dora (2003)
The essential oil of Myrrhinium atropurpureum Schott var. octandrum Bentham was analysed by means of GC and GC–MS. From 24 identiﬁed compounds, representing 95.6% of the oils, α‐pinene was the major component. The oil showed antimicrobial activity against Gram‐positive bacteria. Copyright © 2003 John Wiley & Sons, Ltd.